Skill-biased technological change in Denmark : a disaggregate perspective - Nikolaj Malchow-Møller; Jan Rose Skaksen (Institute for the Study of Labor (IZA), 2003)
In this paper, we provide an industry-level analysis of skill-biased technological change (SBTC) in Denmark over the last two decades. The analysis shows that SBTC has varied considerably across industries, and traditionally large Danish industries have experienced relatively less SBTC. This may partly explain why wage inequality between skilled and less skilled has risen less in Denmark than in other countries. We also find that SBTC has been concentrated in already skill-intensive industries. This contains important information about future labour requirements, as the relative importance of these industries must be expected to grow, thereby reinforcing the shift in demand for skilled labour.
Keywords: J24; L6; J31; 330; skill-biased technological change; Danish industries; Arbeitsnachfrage; Anforderungsprofil; Qualifikation; Technischer Fortschritt; Branche; Lohnstruktur; Schätzung; Dänemark